Efektifitas arang aktif tongkol jagung dalam menurunkan emisi kendaraan bermotor berbahan bakar ganda - H.S. Tira; Y.A. Padang; A. Mulyanto; S. Syahrul; S. Salman; D. Putra (Dinamika Teknik Mesin, 2024)
Emission reduction through after treatment processes has become one of the options to minimize the adverse effects of two-wheeler emissions. Activated charcoal adsorbents have been proven effective in reducing emissions to a certain extent. In this study, corn cob charcoal activated with a 15% NaCl solution serves as the adsorbent. The adsorbent used is shaped into particles with a mesh size of 10. The adsorbent is placed in the modified motorcycle muffler. Testing is conducted on two-wheeled vehicles operated using the dual-fuel method, where biogas and pertalite are used as fuels. With this method, fuel concentrations are obtained significantly smaller compared to vehicles without emission reduction methods. Testing is carried out for 2 hours to determine the durability of the adsorbent in absorbing exhaust gas emissions. Based on the test results, where data collection is conducted every 10 minutes, the concentrations of emissions including hydrocarbons (HC), carbon monoxide (CO), and carbon dioxide (CO2) initially decrease and then rise again after several minutes. This indicates that the adsorbent effectively reduces emissions in a relatively short duration. However, the effectiveness of corn cob activated charcoal in reducing these three emissions varies, with the adsorbent showing good performance in reducing HC